MiRNA-338-3p Inhibits Neuroinflammation in the Corpus Callosum of LCV-LPS Rats Via STAT1 Signal Pathway - Liu, Nan; Zhou, Qiuping; Wang, Huifang; Li, Qian; Chen, Zhuo; Lin, Yiyan; Yi, Lingling; Jiang, Shuqi; Chen, Chunbo; Deng, Yiyu (Cellular and molecular neurobiology, 2023)
Neuroinflammation is a common characteristic of intracranial infection (ICI), which is associated with the activation of astrocytes and microglia. MiRNAs are involved in the process of neuroinflammation. This study aimed to investigate the potential mechanism by which miR-338-3p negatively modulate the occurrence of neuroinflammation. We here reported that the decreased levels of miR-338-3p were detected using qRT-PCR and the upregulated expression of TNF-α and IL-1β was measured by ELISA in the cerebrospinal fluid (CSF) in patients with ICI. A negative association between miR-338-3p and TNF-α or IL-1β was revealed by Pearson correlation analysis. Sprague–Dawley (SD) rats were injected with LPS (50 μg) into left cerebral ventricule (LCV), following which the increased expression of TNF-α and IL-1β and the reduction of miR-338-3p expression were observed in the corpus callosum (CC). Moreover, the expression of TNF-α and IL-1β in the astrocytes and microglia in the CC of LCV-LPS rats were saliently inhibited by the overexpression of miR-338-3p. In vitro , cultured astrocytes and BV2 cells transfected with mimic-miR-338-3p produced less TNF-α and IL-1β after LPS administration. Direct interaction between miR-338-3p and STAT1 mRNA was validated by biological information analysis and dual luciferase assay. Furthermore, STAT1 pathway was found to be implicated in inhibition of neuroinflammation induced by mimic miR-338-3p in the astrocytes and BV2 cells. Taken together, our results suggest that miR-338-3p suppress the generation of proinflammatory mediators in astrocyte and BV2 cells induced by LPS exposure through the STAT1 signal pathway. MiR-338-3p could act as a potential therapeutic strategy to reduce the neuroinflammatory response. Graphical Abstract Diagram describing the cellular and molecular mechanisms associated with LPS-induced neuroinflammation via the miR-338-3p/STAT1 pathway. LPS binds to TLRs on astrocytes or microglia to activate the STAT1 pathway and upregulate the production of pro-inflammatory cytokines. However, miR-338-3p inhibits the expression of STAT1 and reduces the production of inflammatory mediators.